Developing representational competence: linking real-world motion to physics concepts through graphs. (2nd January 2020) - Volkwyn, T. S.; Airey, J.; Gregorcic, B.; Linder, C.
ABSTRACT: A social semiotic lens is used to characterise aspects of representational competence for a discipline such as physics, to provide science teachers with a practical suggestion about how student learning might be organised to develop representational competence. We suggest that representational competence for some areas of science can be characterised in terms of the ability to appropriately interpret and produce a set of disciplinary-scientific representations of real-world phenomena, and link these to scientific concepts. This is because many areas of science are based on creating scientific explanations of real-world observations. We then show how this characterisation may be applied by performing a social semiotic audit of what it entails to become representationally competent in one particular semiotic system (graphs) for one particular area of physics (1-D kinematics). Using this audit, we generate three open-ended tasks expected to help students develop representational competence in this area and empirically demonstrate their potential effectiveness. Building on this example, we suggest that our description of how a disciplinary social semiotic audit may be used to construct open-ended student learning tasks potentially provides one way for teachers to think about the development of representational competence in other semiotic systems and other areas of science.